Die Hüter der Begriffe Politische Sprachen des Konservativen in Großbritannien und der Bundesrepublik Deutschland, 1945-1980 - Steber, Martina (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London, 2017)
What does conservative mean? This question preoccupied intellectuals and politicians in post-1945 Great Britain and West Germany. In the 1960s and 70s, as conservatives sensed they were losing their linguistic authority to the Left, they reinvented the political language of conservatism. This book shows the far-reaching political consequences of this national and trans-national struggle over definitions.